Pengaruh Metode Mind Mapping terhadap Hasil Belajar IPA tentang Gaya pada Siswa Kelas IV SDN Pondok Kopi 03 Pagi Jakarta Timur - Virdiana, Tisya; Ramdani, Akhmad Subkhi (LPPM Universitas Mohammad Husni Thamrin, 2018)
This study used quantitative research through mind mapping methods for grade IV elementary school in Pondok Kopi 03 East Jakarta in order to find out whether there was an effect of the use of mind mapping methods on the learning outcomes of natural science at grade IV elementary school in Pondok Kopi 03 East Jakarta. The purpose of this research was to analyze The Influence of the Mind Mapping Method on the Learning Outcomes of the Natural Science about energy. This research was conducted at the Public Elementary School on Pondok Kopi in West Jakarta. The sample of the research was students at grade IV in the Second semester of elementary school, 2017/2018. The sample was taken using simple random sampling technic. The data was collected by giving multiple choice test, then calculated normality data using liliefors and homogeneity class using barlet. Normality and homogeneity test results indicate that the data is normal and both classes was homogeneous. Subsequently analysed by t test. The results were the value of t count 2,31. Value t table on significance level Î± = 0.05 and dk = 29 is 1,70. Therefore t count value greater than the t table (2,31 > 1,70), the null hypothesis is rejected and accepted working hypothesis. That mean, mind mapping method significantly influence the achievements force on grade IV elementary school.